Unmasking Mediastinal Tuberculosis as an Uncommon Cause of Progressive Dysphagia (Nepal Mediciti Medical Journal, 2025)
Tuberculosis is the most commonly recognized for its pulmonary manifestations; however, its extrapulmonary forms can lead to unusual clinical presentations. We report the case of a 70-year-old male who presented with progressively worsening dysphagia, initially raising clinical suspicion of an esophageal or malignancy-driven obstruction. Comprehensive diagnostic evaluations, including endoscopic ultrasonography and computed tomography, revealed prominent subcarinal and mediastinal lymphadenopathy compressing the esophagus. Endoscopic ultrasonography-guided fine-needle aspiration subsequently confirmed tubercular etiology through cytological and molecular testing. Prompt initiation of anti-tubercular therapy led to rapid symptomatic relief and radiological resolution of the lymphadenopathy. This case highlights the critical need to maintain a high index of suspicion for tuberculosis in patients presenting with dysphagia, particularly in high-burden settings like Nepal. Early recognition and targeted treatment of this potentially overlooked cause of mediastinal lymphadenopathy are essential to avoid unnecessary invasive interventions and ensure optimal patient outcomes.